(untitled) (Journal of Nepal Physical Society, 2024)
Basmati rice, renowned for its exceptional aroma, distinct flavor, and long grains, is a staple in global cuisines. Understanding and enhancing the germination and growth of Basmati rice seeds carry significant implications for both agricultural practices and culinary traditions. This study investigates how plasma-activated water, produced through atmospheric pressure air gliding arc discharge, affects Basmati rice seeds’ germination and growth parameters. The physiochemical analysis reveals a progressive increase in water acidity, electrical conductivity, oxidation-reduction potential, total dissolved solids, and nitrate/nitrite concentrations as treatment time extends from 0 to 20 minutes. The results highlight a significant impact of plasma-activated water on Basmati rice germination and seedling growth. The seed imbibition rate rises with longer plasma activation, reaching a peak at 10 minutes, leading to maximum seed germination, extended seedling shoots, and increased plant weight compared to the control group. However, prolonged exposure (20 minutes) shows adverse effects on seed germination and growth. These findings contribute valuable insights into the potential applications and limitations of plasma-activated water in Basmati rice.